JAK2, STAT3 Gene Polymorphisms in Turkish Patients with Behçet’s Disease - Darya Farhoomand Aksoy; Rahime Aksoy; Sevim Gönen; Ümit Ölmez (Gazi Medical Journal)
Objective: Behçet’s disease (BD) is a chronic, multisystemic inflammatory disorder with an unknown etiology. T cells are crucial in the pathogenesis of BD. Janus kinase-2 (JAK2) and signal transducer and activator of transcription 3 (STAT3) are intracellular signal transduction molecules that increase the risk of developing some autoimmune diseases. By modifying Th1 and Th17 responses, the JAK2 and STAT3 signaling pathways are believed to be effective in BD. This study aimed to determine whether BD in the Turkish population is related to JAK2 and STAT3 polymorphisms. Methods: A case-control study included a total of 197 patients with BD who were referred to the Ankara University Faculty of Medicine and 100 healthy individuals without a history of autoimmune disease or BD in their family or themselves. The genotypes of one single-nucleotide polymorphism (SNPs) (rs10974944) in JAK2 and one SNPs (rs2293152) in the STAT3 gene were analyzed using polymerase chain reaction restriction fragment length polymorphism. Results: The result of this investigation identified that in this disease, there was a significantly increased frequency of the CG genotype of the rs10974944 JAK2 in patients with BD compared with a control group (p=0.031, odds ratio [95% confidence interval: 0.392 (0.163- 0.942)]. None of the tested SNPs (rs2293152) of STAT3 were associated with BD. Conclusion: This is the first investigation into JAK2 and STAT3 polymorphisms in Turkish patients with BD. These results suggest that a JAK2 genetic polymorphism may be associated with BD susceptibility.